Low-temperature polymer lithium battery and preparation method thereof

By using polyethylene oxide self-polymerization in lithium batteries, adding doped modified LLZO nanoparticles, and using triethylene glycol dimethyl ether as plasticizer, the problem of degradation of lithium batteries in low temperature environments is solved, and efficient discharge and excellent cycle stability are achieved.

CN119764546AActive Publication Date: 2025-04-04GUANGDONG HONGJIE NEW ENERGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411993445.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The performance of traditional lithium batteries in low temperature environments has significantly decreased, resulting in limited application in cold areas. The main problems are the increase in viscosity of the electrolyte, the decrease in conductivity, and the slowdown in the migration rate of lithium ions, resulting in a decrease in discharge performance and cycling stability.

Method used

Polyethylene oxide is used as a monomer to prepare a polymer electrolyte membrane through self-polymerization, and inorganic nanoparticles such as LLZO are added to the membrane. The electrochemical performance of LLZO is improved by doping modification of aluminum, gallium, tantalum and niobium. At the same time, triethylene glycol dimethyl ether is used as a plasticizer to optimize the solid electrolyte formula.

Benefits of technology

It improves the discharge performance and cycle stability of lithium batteries in extremely low temperature environments, enhances the safety and mechanical strength of the batteries, and ensures the efficient operation of the batteries under low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224096750000141
    Figure BDA0005224096750000141
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a low-temperature polymer lithium battery and a preparation method thereof. The low-temperature polymer lithium battery comprises a positive plate, a negative plate, a polymer electrolyte membrane and a battery shell, by preparing the polymer electrolyte membrane and optimizing a solid electrolyte formula, the low-temperature polymer lithium battery which is high in ionic conductivity, capable of keeping good discharge performance in an extremely low-temperature environment, excellent in cycling stability and high in safety is prepared; the method has important significance for promoting the development of related industries in cold regions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a low-temperature polymer lithium battery and a preparation method thereof. Background Art

[0002] With the rapid development of modern science and technology, lithium batteries, as key components for energy storage and power supply, have been widely used in consumer electronics, electric vehicles, aerospace and other fields. However, the performance of traditional lithium batteries decreases significantly in low temperature environments, which limits their application in cold areas. As the temperature decreases, the viscosity of the electrolyte increases significantly, resulting in a decrease in conductivity and a slowdown in the migration rate of ions in the electrolyte, which affects the discharge performance of the battery. In low temperature environments, the auxiliary materials in the positive and negative electrode materials inside the battery may undergo vitrification, which hinders the conduction of lithium ions, resulting in an increase in the internal resistance of the battery and a decrease in performance. At low temperatures, the number of ion channels inside the battery decreases, and the diffusion rate of ions in the material decreases, further affecting the discharge efficiency and cycle stability of the battery.

[0003] Therefore, developing a low-temperature polymer lithium battery with high ionic conductivity, good discharge performance in extremely low temperature environments, excellent cycle stability and high safety is of great significance for promoting the development of related industries in cold regions. Summary of the invention

[0004] The object of the present invention is to provide a low-temperature polymer lithium battery and a preparation method thereof. The low-temperature polymer lithium battery has high ion conductivity, can maintain good discharge performance in an extremely low temperature environment, has excellent cycle stability and high safety.

[0005] A low-temperature polymer lithium battery comprises a positive electrode sheet, a negative electrode sheet, a polymer electrolyte membrane and a battery shell.

[0006] The raw materials for preparing the positive electrode sheet include positive electrode active material, conductive agent, adhesive and N-methylpyrrolidone.

[0007] Preferably, the mass ratio of the positive electrode active material, the conductive agent and the adhesive is 8:1:1.

[0008] Preferably, the positive electrode active material includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium cobaltate, and lithium iron phosphate; more preferably, it is lithium iron phosphate.

[0009] Preferably, the conductive agent includes one or more of conductive graphite, acetylene black, superconducting carbon, and conductive carbon black; further preferably, it is conductive carbon black.

[0010] Preferably, the particle size of the conductive carbon black is 25-35 nm, and the ash content is ≤0.01%.

[0011] In some preferred embodiments, the conductive carbon black is purchased from Tianjin Baochi Chemical Technology Co., Ltd.

[0012] Preferably, the binder comprises polyvinylidene fluoride.

[0013] The polyvinylidene fluoride has a melting index of 0.5-2.0 g / 10 min at 230° C., a melting point of 156-165° C., and a water content of ≤0.1%.

[0014] In some preferred embodiments, the polyvinylidene fluoride is purchased from Arkema, France, PNDF 760.

[0015] Preferably, the negative electrode sheet is a lithium sheet.

[0016] Preferably, the battery shell is a button battery shell, CR2025 type.

[0017] The preparation method of the polymer electrolyte membrane comprises the following steps: uniformly mixing polyethylene oxide, lithium salt and plasticizer, adding inorganic nanoparticles for ball milling, spreading the ball-milled slurry on a glass plate, and drying it in argon at 100-120° C. for 2-5 hours to obtain the polymer electrolyte membrane.

[0018] Preferably, the thickness of the polymer electrolyte membrane is 30-40 μm.

[0019] Preferably, the average relative molecular mass of the polyethylene oxide is 100,000, and the viscosity of a 5% polyethylene oxide aqueous solution at 25° C. is 15-50 cp.

[0020] In some preferred embodiments, the polyethylene oxide is purchased from Sigma-Aldrich (Shanghai) Co., Ltd.

[0021] Selecting polyethylene oxide as a monomer and preparing a polymer electrolyte membrane by self-polymerization can not only improve the safety of lithium batteries, but also improve their low temperature resistance. This may be because on the one hand, polyethylene oxide electrolyte has a stable crystal structure, which makes it difficult for lithium ions to form dendritic structures (lithium dendrites) during migration, thereby effectively avoiding the risk of battery short circuit and explosion. In addition, solid electrolytes themselves have higher safety than liquid electrolytes. On the other hand, polyethylene oxide electrolytes can maintain good performance over a wide temperature range, and even in low temperature environments, the migration speed of lithium ions will not be greatly affected, thereby ensuring the low temperature performance of the battery. And polyethylene oxide electrolytes have good compatibility with lithium metal negative electrodes, which helps to improve the electrochemical performance of batteries. However, polyethylene oxide has a high degree of crystallinity at room temperature, which interferes with the movement of polymer segments and lithium ions, resulting in poor conductivity of polyethylene oxide-based polymer electrolytes at the operating temperature of lithium metal batteries, affecting the overall performance of the battery. In addition, polyethylene oxide has relatively low mechanical strength and weak resistance to puncture short circuits, which may affect the safety and stability of the battery.

[0022] Preferably, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, and lithium tetrafluoroborate.

[0023] Preferably, the plasticizer includes one or more of butyronitrile, dimethyl carbonate, ethylene carbonate, N,N-dimethylformamide, propylene carbonate, fluoroethylene carbonate, and triethylene glycol dimethyl ether; further preferably, triethylene glycol dimethyl ether.

[0024] Nitrile is a commonly used plasticizer, but its unstable interface contact with lithium negative electrode limits its application. By selecting triethylene glycol dimethyl ether as a plasticizer and controlling its addition amount, not only can the ionic conductivity of polyethylene oxide polymer electrolyte membrane be improved, but also the electrochemical performance and cycle life of lithium ion batteries can be improved. This may be because triethylene glycol dimethyl ether can not only reduce the crystallinity of polyethylene oxide, making the polymer chain segment more flexible, which is conducive to the migration of lithium ions, thereby improving ionic conductivity, but also improve the compatibility between polyethylene oxide polymer electrolyte membrane and electrode materials, and help form a stable electrolyte / electrode interface, thereby improving the cycle performance of the battery.

[0025] Preferably, the mass ratio of the polyethylene oxide to the inorganic nanoparticles is (1-3):1.

[0026] By adding inorganic nanoparticles, especially LLZO, not only can more ion channels be formed in the polymer electrolyte membrane, which helps the migration of lithium ions and thus improves the ionic conductivity of the PEO polymer electrolyte membrane, but also the mechanical strength of the PEO polymer electrolyte membrane can be enhanced, and its ability to resist puncture and short circuit can be improved, thereby enhancing the safety and stability of the battery. In addition, LLZO particles can form a good interface contact with the electrode material, which helps to reduce the interface resistance and improve the electrochemical performance of the battery. However, the ionic conductivity of traditional LLZO inorganic nanoparticles is also low, which has limited improvement on the overall electrochemical performance of the battery and poor stability in the air.

[0027] Preferably, the added amount of the lithium salt is 2%-5% of the mass of the polyethylene oxide.

[0028] Preferably, the added amount of the plasticizer is 15%-20% of the total mass of the polyethylene oxide and the inorganic nanoparticles.

[0029] Preferably, the ball milling speed is 200-300 rpm, and the ball milling time is 5-8 h.

[0030] The method for preparing the inorganic nanoparticles comprises the following steps:

[0031] S1. Mix lithium hydroxide, lanthanum nitrate, zirconium acetate, aluminum nitrate, gallium oxide, tantalum pentoxide, niobium pentoxide and weak acid, add dilute nitric acid dropwise until no precipitation occurs, stir at 70-80°C for 10-15h to form a uniform gel, heat to 150-200°C and dry for 1-2h, sinter in steps, and grind to a particle size of <100nm to obtain substance 1;

[0032] S2. Dissolve the silane coupling agent in an ethanol aqueous solution and adjust the pH value of the system to 4-5, add substance 1, stir at 50-60°C for 6-8h, centrifuge, wash with anhydrous ethanol 2-3 times, and vacuum dry at 50-60°C to constant weight to obtain.

[0033] Preferably, the weak acid includes one or more of citric acid, tartaric acid and acetic acid; further preferably, it is citric acid.

[0034] Before adding dilute nitric acid to dissolve the metal salt, adding an appropriate amount of citric acid can not only improve the stability of the gel, thereby improving the quality of the prepared inorganic nanoparticles, but also improve the battery cycle life. This may be because on the one hand, citric acid can not only adjust the pH value of the reactants, thereby adjusting the stability of the sol, but also form a coordination complex with metal ions, which helps to stabilize the dispersion of metal ions in the sol and prevents the hydrolysis and precipitation of metal ions from hindering the reaction. On the other hand, adding an appropriate amount of citric acid can form a dispersed coating on the surface of the material, slowing down the diffusion rate of lithium ions, thereby reducing the degradation rate of battery materials and improving the battery cycle life.

[0035] Preferably, the molar ratio of lithium hydroxide, lanthanum nitrate, zirconium acetate, aluminum nitrate, gallium oxide, tantalum pentoxide, niobium pentoxide and weak acid is (7.5-8.5):(2.8-3.2):(1.3-1.6):(0.1-0.3):(0.1-0.3):(0.2-0.3):(0.2-0.3):(4.5-5.5); further preferably, it is 8:3:1.5:0.2:0.2:0.25:0.25:5.

[0036] By selecting aluminum, gallium, tantalum, and niobium to dope LLZO, not only can its electrochemical performance be improved, but also the density and stability of inorganic nanoparticles can be improved. This may be because Al doping affects the lattice structure of LLZO by generating lithium ion vacancies, which helps the migration of lithium ions and stabilizes the cubic phase LLZO, which usually has higher conductivity. Ga doping improves the migration efficiency of lithium ions by regulating the occupancy rate of lithium ions in octahedral vacancies and optimizing the grain size and bottleneck size. The co-doping of Al and Ga synergistically further improves the ionic conductivity of LLZO. Ta doping not only improves the ionic conductivity of LLZO by changing the lattice structure and lithium ion migration channels of LLZO, but also changes the occupancy of Al in LLZO, thereby providing more space for lithium ion migration. In addition, the co-doping of Al and Ta can more easily stabilize the cubic phase LLZO and reduce the formation of tetragonal phase. Nb doping can also improve the ionic conductivity of LLZO by affecting the lattice structure and ion occupancy. The four elements work synergistically to further improve the performance of LLZO by stabilizing the cubic phase LLZO, optimizing the lithium ion migration channel and improving the ionic conductivity, thereby improving the stability and electrochemical performance of polymer electrolytes and lithium-ion batteries. In addition, Al doping can reduce the densification temperature of LLZO, while Ga doping can make LLZO obtain higher density and ionic conductivity at a lower sintering temperature, so that LLZO with excellent performance can be obtained at a lower sintering temperature, saving energy. However, the poor interfacial compatibility between inorganic nanoparticles and polymer matrices affects the performance of polymer electrolytes and lithium-ion batteries.

[0037] Preferably, the concentration of the dilute nitric acid is 3-5 mol / L.

[0038] The specific steps of the step-by-step sintering are: heating to 250-300°C at a rate of 5°C / min and keeping warm for 1.5-2.5h; heating to 750-800°C at a rate of 5°C / min and keeping warm for 8-12h; heating to 1100-1150°C at a rate of 5°C / min and keeping warm for 1-2h, and cooling to room temperature at a rate of 10°C / min.

[0039] Through three-stage sintering, LLZO crystal defects can be reduced and the overall quality and performance of the sample can be improved. The first calcination at a lower temperature helps to remove adsorbed water, crystallization water and possible volatile impurities in the raw materials. The second calcination at a medium temperature can further promote the formation of LLZTO crystal nuclei and initial crystal growth. The calcination time at this stage is relatively long, which helps to stabilize and uniformly distribute the crystal structure. At the same time, this step can continue to remove residual impurities and improve the purity of the sample. The third calcination at a higher temperature accelerates the growth and densification process of the crystal to form an LLZTO sample with excellent performance. In addition, high-temperature calcination can also eliminate pores and defects in the sample and improve the overall quality and performance of the sample.

[0040] Preferably, the silane coupling agent includes one or more of glycidyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, and γ-aminopropyltriethoxysilane; further preferably, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0041] Preferably, the mass ratio of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane to γ-aminopropyltriethoxysilane is (1-3):1; more preferably, it is 2:1.

[0042] The use of a specific silane coupling agent to strengthen the surface of LLZO after element doping modification can further improve the electrochemical performance and stability of lithium-ion batteries. This may be because the two silane coupling agents work synergistically. On the one hand, they combine with the surface of the doped and modified LLZO through chemical bonding to form a strong interface layer, which not only improves the mechanical strength of the polymer electrolyte membrane, but also reduces the charge transfer resistance at the interface. On the other hand, the epoxy group of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and the amino group of γ-aminopropyltriethoxysilane have good compatibility with organic polymer materials such as polyethylene oxide, and can closely combine inorganic substances and organic polymer materials through chemical reactions or physical entanglement to form a continuous and dense interface layer, which is conducive to the transmission of lithium ions and the stability of the electrolyte. By optimizing the interface structure, the two silane coupling agents can significantly improve the electrochemical performance of lithium-ion batteries, reduce the polarization degree of the battery, and increase the migration rate of lithium ions and the cycle stability of the battery. At the same time, they can also reduce side reactions at the interface and extend the service life of the battery.

[0043] Preferably, the volume concentration of ethanol in the ethanol aqueous solution is 60% to 70%.

[0044] Preferably, the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:40-50.

[0045] Preferably, the mass ratio of the silane coupling agent to substance one is (1.5-2.5):1.

[0046] The method for preparing the low-temperature polymer lithium battery comprises the following steps:

[0047] A1. Mix the positive electrode active material and the conductive agent and put them into a ball mill. After ball milling for 30-50 minutes at a speed of 200-300 rpm, add a binder, and drop N-methylpyrrolidone and continue grinding for 50-60 minutes. Then, apply it on the current collector and put it in a vacuum oven at 85°C to dry for 24 hours to obtain a positive electrode sheet.

[0048] A2. Place the positive electrode sheet and polymer electrolyte membrane in the bottom of the battery case in turn, then put in the lithium sheet, cover with the top cover to seal, the battery assembly pressure is 1kPa, the pressure holding time is 10s, after the assembly is completed, let it stand for 2-3h.

[0049] Preferably, the added amount of N-methylpyrrolidone is 4-5 times the mass of the positive electrode active material.

[0050] Preferably, the purpose of drying in a vacuum oven at 85° C. for 24 h (reduced pressure drying) is to remove N-methylpyrrolidone.

[0051] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0052] 1. The present invention provides a low-temperature polymer lithium battery. By preparing a polymer electrolyte membrane and optimizing the solid electrolyte formula, a low-temperature polymer lithium battery with high ion conductivity, good discharge performance in an extremely low temperature environment, excellent cycle stability and high safety is prepared. This is of great significance for promoting the development of related industries in cold regions.

[0053] 2. The present invention uses polyethylene oxide as a monomer and prepares a polymer electrolyte membrane by self-polymerization, which can not only improve the safety of the lithium battery, but also improve its low temperature resistance.

[0054] 3. The present invention, by adding inorganic nanoparticles, especially LLZO, can not only form more ion channels in the polymer electrolyte membrane, which is conducive to the migration of lithium ions, thereby improving the ionic conductivity of the PEO polymer electrolyte membrane, but also enhance the mechanical strength of the PEO polymer electrolyte membrane and improve its ability to resist puncture short circuits, thereby enhancing the safety and stability of the battery.

[0055] 4. The present invention adopts aluminum, gallium, tantalum and niobium to dope LLZO, which can not only improve its electrochemical performance, but also improve the density and stability of inorganic nanoparticles.

[0056] 5. The present invention uses a specific silane coupling agent to strengthen the surface of the element-doped modified LLZO, which can further improve the electrochemical performance and stability of the lithium-ion battery.

[0057] 6. The present invention selects triethylene glycol dimethyl ether as a plasticizer and controls its addition amount, which can not only improve the ionic conductivity of the polyethylene oxide polymer electrolyte membrane, but also improve the electrochemical performance and cycle life of the lithium ion battery. DETAILED DESCRIPTION

[0058] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] The raw materials used in the present invention are all commercially available, specifically:

[0060] The particle size of the conductive carbon black was 25-35 nm, the ash content was ≤0.01%, and it was purchased from Tianjin Baochi Chemical Technology Co., Ltd.

[0061] Polyvinylidene fluoride, with a melt index of 0.5-2.0 g / 10 min at 230° C., a melting point of 156-165° C., and a moisture content of ≤0.1%, was purchased from Arkema, France, PNDF 760.

[0062] The average relative molecular mass of polyethylene oxide is 100000, and the viscosity of a 5% polyethylene oxide aqueous solution at 25° C. is 15-50 cp. The polyethylene oxide was purchased from Sigma-Aldrich (Shanghai) Co., Ltd.

[0063] Example 1

[0064] This embodiment provides a low-temperature polymer lithium battery, including a positive electrode sheet, a negative electrode sheet, and a polymer electrolyte membrane.

[0065] The raw materials for preparing the positive electrode sheet are positive electrode active material, conductive agent, adhesive and N-methylpyrrolidone.

[0066] The mass ratio of the positive electrode active material, the conductive agent and the adhesive is 8:1:1.

[0067] The positive electrode active material is lithium iron phosphate.

[0068] The conductive agent is conductive carbon black.

[0069] The negative electrode sheet is a lithium sheet.

[0070] The battery case is a button battery case, CR2025 type.

[0071] The preparation method of the polymer electrolyte membrane comprises the following steps: uniformly mixing polyethylene oxide, lithium salt and plasticizer, adding inorganic nanoparticles for ball milling, spreading the ball-milled slurry on a glass plate, and drying it under argon gas at 110° C. for 4 hours to obtain the polymer electrolyte membrane.

[0072] The thickness of the polymer electrolyte membrane was 35 μm.

[0073] The lithium salt is lithium bis(trifluoromethanesulfonyl)imide, and the added amount is 4% of the mass of polyethylene oxide.

[0074] The plasticizer is triethylene glycol dimethyl ether, and the added amount is 18% of the total mass of polyethylene oxide and inorganic nanoparticles.

[0075] The mass ratio of the polyethylene oxide to the inorganic nanoparticles is 2:1.

[0076] The rotation speed of the ball mill is 250 rpm, and the ball milling time is 6 h.

[0077] The preparation method of the inorganic nanoparticles comprises the following steps:

[0078] S1. Mix lithium hydroxide, lanthanum nitrate, zirconium acetate, aluminum nitrate, gallium oxide, tantalum pentoxide, niobium pentoxide and weak acid, add dilute nitric acid dropwise until no precipitation occurs, stir at 75°C for 12 hours to form a uniform gel, heat to 180°C and dry for 1.5 hours, sinter in steps, and grind to a particle size of <100 nm to obtain substance 1;

[0079] S2. Dissolve the silane coupling agent in an ethanol aqueous solution and adjust the pH value of the system to 4, add substance 1, stir at 55°C for 7 hours, centrifuge, wash with anhydrous ethanol for 3 times, and vacuum dry at 55°C to constant weight to obtain.

[0080] The weak acid is citric acid.

[0081] The molar ratio of the lithium hydroxide, lanthanum nitrate, zirconium acetate, aluminum nitrate, gallium oxide, tantalum pentoxide, niobium pentoxide and weak acid is 8:3:1.5:0.2:0.2:0.25:0.25:5.

[0082] The concentration of the dilute nitric acid is 4 mol / L.

[0083] The specific steps of the step-by-step sintering are: heating to 280°C at a rate of 5°C / min and keeping warm for 2 hours; heating to 780°C at a rate of 5°C / min and keeping warm for 10 hours; heating to 1120°C at a rate of 5°C / min and keeping warm for 1.5 hours, and cooling to room temperature at a rate of 10°C / min.

[0084] The silane coupling agent is 3-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane, and the mass ratio is 2:1.

[0085] The volume concentration of ethanol in the ethanol aqueous solution is 65%.

[0086] The mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:45.

[0087] The mass ratio of the silane coupling agent to substance one is 2:1.

[0088] The method for preparing the low-temperature polymer lithium battery comprises the following steps:

[0089] A1. Mix the positive electrode active material and the conductive agent and put them into a ball mill. After ball milling at a speed of 250 rpm for 40 minutes, add a binder and drop N-methylpyrrolidone. Continue grinding for 55 minutes, apply it on the current collector, and put it in a vacuum oven at 85°C to dry for 24 hours to obtain a positive electrode sheet.

[0090] A2. Place the positive electrode sheet and polymer electrolyte membrane in the bottom of the battery case in turn, then put in the lithium sheet, cover with the top cover to seal, the battery assembly pressure is 1kPa, the pressure holding time is 10s, after the assembly is completed, let it stand for 3h.

[0091] The added amount of N-methylpyrrolidone is 5 times the mass of the positive electrode active material.

[0092] Example 2

[0093] The difference between this embodiment and embodiment 1 is that the mass ratio of the polyethylene oxide to the inorganic nanoparticles is 5:2.

[0094] Comparative Example 1

[0095] The difference between this comparative example and Example 1 is that the preparation method of the polymer electrolyte membrane comprises the following steps: after polyethylene oxide and lithium salt are uniformly mixed, inorganic nanoparticles are added for ball milling, the ball-milled slurry is spread on a glass plate, and dried under argon gas at 110° C. for 4 hours to obtain the polymer electrolyte membrane.

[0096] Comparative Example 2

[0097] The difference between this comparative example and Example 1 is that the plasticizer is acetonitrile, and the added amount is 18% of the total mass of polyethylene oxide and inorganic nanoparticles.

[0098] Comparative Example 3

[0099] The difference between this comparative example and Example 1 is that the preparation method of the inorganic nanoparticles comprises the following steps:

[0100] S1. After mixing lithium hydroxide, lanthanum nitrate, zirconium acetate, gallium oxide, tantalum pentoxide, niobium pentoxide and weak acid, add dilute nitric acid dropwise until no precipitation occurs, stir at 75°C for 12 hours to form a uniform gel, heat to 180°C and dry for 1.5 hours, sinter in steps, and grind to a particle size of <100 nm to obtain substance 1;

[0101] S2. Dissolve the silane coupling agent in an ethanol aqueous solution and adjust the pH value of the system to 4, add substance 1, stir at 55°C for 7 hours, centrifuge, wash with anhydrous ethanol for 3 times, and vacuum dry at 55°C to constant weight to obtain.

[0102] The molar ratio of the lithium hydroxide, lanthanum nitrate, zirconium acetate, gallium oxide, tantalum pentoxide, niobium pentoxide and weak acid is 8:3:1.5:0.2:0.25:0.25:5.

[0103] Comparative Example 4

[0104] The difference between this comparative example and Example 1 is that the preparation method of the inorganic nanoparticles comprises the following steps:

[0105] S1. After mixing lithium hydroxide, lanthanum nitrate, zirconium acetate, aluminum nitrate, gallium oxide, niobium pentoxide and weak acid, add dilute nitric acid dropwise until no precipitation occurs, stir at 75°C for 12 hours to form a uniform gel, heat to 180°C and dry for 1.5 hours, sinter in steps, and grind to a particle size of <100 nm to obtain substance 1;

[0106] S2. Dissolve the silane coupling agent in an ethanol aqueous solution and adjust the pH value of the system to 4, add substance 1, stir at 55°C for 7 hours, centrifuge, wash with anhydrous ethanol for 3 times, and vacuum dry at 55°C to constant weight to obtain.

[0107] The molar ratio of the lithium hydroxide, lanthanum nitrate, zirconium acetate, aluminum nitrate, gallium oxide, niobium pentoxide and weak acid is 8:3:1.5:0.2:0.2:0.25:5.

[0108] Comparative Example 5

[0109] The difference between this comparative example and Example 1 is that the preparation method of the inorganic nanoparticles comprises the following steps:

[0110] S1. After mixing lithium hydroxide, lanthanum nitrate, zirconium acetate, aluminum nitrate, gallium oxide, tantalum pentoxide and niobium pentoxide, dilute nitric acid is added dropwise until no precipitation occurs, and the mixture is stirred at 75°C for 12 hours to form a uniform gel. The mixture is heated to 180°C and dried for 1.5 hours. After step-by-step sintering, the mixture is crushed and ground to a particle size of <100 nm to obtain substance 1.

[0111] S2. Dissolve the silane coupling agent in an ethanol aqueous solution and adjust the pH value of the system to 4, add substance 1, stir at 55°C for 7 hours, centrifuge, wash with anhydrous ethanol for 3 times, and vacuum dry at 55°C to constant weight to obtain.

[0112] Comparative Example 6

[0113] The difference between this comparative example and Example 1 is that the specific steps of the step-by-step sintering are: heating to 280°C at a rate of 5°C / min and keeping warm for 2h; heating to 780°C at a rate of 5°C / min and keeping warm for 10h, and cooling to room temperature at a rate of 10°C / min.

[0114] Comparative Example 7

[0115] The difference between this comparative example and Example 1 is that the preparation method of the inorganic nanoparticles comprises the following steps: mixing lithium hydroxide, lanthanum nitrate, zirconium acetate, aluminum nitrate, gallium oxide, tantalum pentoxide, niobium pentoxide and a weak acid, adding dilute nitric acid dropwise until no precipitation occurs, stirring at 75°C for 12 hours to form a uniform gel, heating to 180°C and drying for 1.5 hours, sintering in steps, and then crushing and grinding to a particle size of <100 nm to obtain the obtained nanoparticles.

[0116] Comparative Example 8

[0117] The difference between this comparative example and Example 1 is that the silane coupling agent is 3-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0118] Performance Testing

[0119] The battery impedance was tested by electrochemical impedance spectroscopy and its ionic conductivity was calculated. The voltage amplitude was 15 mV, the frequency range was 0.5 to 1.5 MHz, and the test temperature was -20°C. Cyclic performance test at 25°C and -20°C: The battery was charged to 4.5 V at 0.5 C constant current and constant voltage, with a cut-off current of 0.05 C, and then discharged to 3.0 V at 0.1 C constant current. After 500 cycles of charge and discharge, the capacity retention rate at the 500th week was calculated as (initial capacity - capacity after 500 cycles) / initial capacity × 100%. The capacity retention rate at 25°C and -20°C was calculated. The results are shown in Table 1.

[0120] Table 1 Measurement results

[0121]

[0122] According to statistics, the low-temperature polymer lithium battery prepared by Examples 1 to 2 of the present invention has a high ion conductivity and good cycle stability at both room temperature and low temperature. No plasticizer was added in Comparative Example 1, acetonitrile was used as the plasticizer in Comparative Example 2, aluminum was not used for doping in Comparative Example 3, tantalum was not used for doping in Comparative Example 4, weak acid was not added in Comparative Example 5, high-temperature sintering was not performed in Comparative Example 6, LLZO after doping was not modified in Comparative Example 7, and γ-aminopropyltriethoxysilane was not added to modify LLZO after doping in Comparative Example 8. The prepared low-temperature polymer lithium battery has poor performance. Therefore, the low-temperature polymer lithium battery prepared by the raw materials and methods described in this application has high ion conductivity, can maintain good discharge performance in an extremely low temperature environment, and has excellent cycle stability and high safety.

[0123] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A low-temperature polymer lithium battery, characterized in that: Including positive electrode sheet, negative electrode sheet, polymer electrolyte membrane and battery shell; The raw materials for preparing the positive electrode sheet include positive electrode active material, conductive agent, adhesive, and N-methylpyrrolidone; The preparation method of the polymer electrolyte membrane comprises the following steps: after polyethylene oxide, lithium salt and plasticizer are uniformly mixed, inorganic nanoparticles are added for ball milling, the ball-milled slurry is spread on a glass plate, and dried for 2-5 hours under argon gas at 100-120° C. to obtain the polymer electrolyte membrane; The method for preparing the inorganic nanoparticles comprises the following steps: S1. Mix lithium hydroxide, lanthanum nitrate, zirconium acetate, aluminum nitrate, gallium oxide, tantalum pentoxide, niobium pentoxide and weak acid, add dilute nitric acid dropwise until no precipitation occurs, stir at 70-80°C for 10-15h to form a uniform gel, heat to 150-200°C and dry for 1-2h, sinter in steps, and grind to a particle size of <100nm to obtain substance 1; S2. Dissolve the silane coupling agent in an ethanol aqueous solution and adjust the pH value of the system to 4-5, add substance 1, stir at 50-60°C for 6-8h, centrifuge, wash with anhydrous ethanol 2-3 times, and vacuum dry at 50-60°C to constant weight to obtain.

2. The low-temperature polymer lithium battery according to claim 1, characterized in that: The raw materials for preparing the positive electrode sheet include positive electrode active material, conductive agent and adhesive.

3. The low-temperature polymer lithium battery according to claim 1, characterized in that: The average relative molecular mass of the polyethylene oxide is 100,000, and the viscosity of a 5% polyethylene oxide aqueous solution at 25° C. is 15-50 cp.

4. The low-temperature polymer lithium battery according to claim 1, characterized in that: The plasticizer includes one or more of nitrile, dimethyl carbonate, ethylene carbonate, N,N-dimethylformamide, propylene carbonate, fluoroethylene carbonate, and triethylene glycol dimethyl ether.

5. The low-temperature polymer lithium battery according to claim 1, characterized in that: The molar ratio of the lithium hydroxide, lanthanum nitrate, zirconium acetate, aluminum nitrate, gallium oxide, tantalum pentoxide, niobium pentoxide and weak acid is (7.5-8.5):(2.8-3.2):(1.3-1.6):(0.1-0.3):(0.1-0.3):(0.2-0.3):(0.2-0.3):(4.5-5.5).

6. The low-temperature polymer lithium battery according to claim 1, characterized in that: The specific steps of the step-by-step sintering are: heating to 250-300°C at a rate of 5°C / min and keeping warm for 1.5-2.5h; heating to 750-800°C at a rate of 5°C / min and keeping warm for 8-12h; heating to 1100-1150°C at a rate of 5°C / min and keeping warm for 1-2h, and cooling to room temperature at a rate of 10°C / min.

7. The low-temperature polymer lithium battery according to claim 1, characterized in that: The silane coupling agent includes one or more of glycidyltrimethoxysilane, 3-(2,3-glycidyloxy)propyltrimethoxysilane, and γ-aminopropyltriethoxysilane; more preferably, 3-(2,3-glycidyloxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane.

8. The low-temperature polymer lithium battery according to claim 1, characterized in that: The weak acid includes one or more of citric acid, tartaric acid and acetic acid.

9. The low-temperature polymer lithium battery according to claim 1, characterized in that: The lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, and lithium tetrafluoroborate.

10. A method for preparing a low-temperature polymer lithium battery according to any one of claims 1 to 9, characterized in that: The following steps are involved: A1. Mix the positive electrode active material and the conductive agent and put them into a ball mill. After ball milling for 30-50 minutes at a speed of 200-300 rpm, add a binder, and drop N-methylpyrrolidone and continue grinding for 50-60 minutes. Then, apply it on the current collector and put it in a vacuum oven at 85°C to dry for 24 hours to obtain a positive electrode sheet. A2. Place the positive electrode sheet and polymer electrolyte membrane in the bottom of the battery case in turn, then put in the lithium sheet, cover with the top cover to seal, the battery assembly pressure is 1kPa, the pressure holding time is 10s, after the assembly is completed, let it stand for 2-3h.

Citation Information

Patent Citations

  • Alkyl silicyl lithium battery polymer electrolyte resistant to high voltage, preparation method and application thereof in all-solid-state lithium battery

    CN108242563A

  • Preparation method of low-temperature flexible polymer solid electrolyte membrane and application of electrolyte membrane to low-temperature solid lithium ion battery

    CN109411809A

  • PEO polymer solid electrolyte with high safety performance, preparation method of PEO polymer solid electrolyte and solid lithium battery

    CN114628768A

  • High-temperature-resistant flame-retardant PVDF-based semi-solid electrolyte and preparation method thereof

    CN118983513A

  • Polymer electrolyte membrane including boronnitride, method of preparing the same, and litium secondary battery including the same

    KR101911070B1